Collective dynamics in noble-gas and other very simple classical fluids - Bafile, U.; Barocchi, F.; Guarini, E. (Condensed Matter Physics, 2008)
Rare gases and their liquids are the simplest systems to study for accurate investigations of the collective
dynamics of fluid matter. Much work has been done using different spectroscopic techniques, moleculardynamics
simulations, and theoretical developments, in order to gain insight into the microscopic processes
involved, in particular, in the propagation of acoustic excitations in gases and liquids. Here we briefly review
the interpretation schemes currently applied to the characterization of such excitations, and recall a few results
obtained from the analysis of rare-gas fluids and other very simple systems. Iнертнi гази та їхнi рiдини є найпростiшими системами для точних дослiджень колективної динамiки плинiв. Було пророблено значну роботу з використанням рiзноманiтних спектроскопiчних методик, моделювання методом молекулярної динамiки та теоретичних розробок для розумiння мiкроскопiчних процесiв, що приймають участь у поширеннi звукових збуджень у газах та рiдинах. Ми подаємо короткий огляд iнтерпретацiйних схем, що застосовуються для опису таких збуджень, та нагадуємо декiлька результатiв, отриманих iз аналiзу плинiв iнертних газiв та iнших дуже простих систем.